A new composite gel polymer electrolyte based on matrix of PEGDA with high ionic conductivity for lithium-ion batteries. (10th September 2020) - Liu, Meng; Wang, Yue; Li, Meng; Li, Guangqi; Li, Bin; Zhang, Songtong; Ming, Hai; Qiu, Jingyi; Chen, Junhong; Zhao, Pengcheng
Abstract: New gel polymer electrolytes (GPEs) based on poly (ethylene glycol) diacrylate (PEGDA) were prepared through an in-situ thermal polymerization method in liquid electrolyte. Different from previous reports, PEGDA was utilized as a matrix instead of a cross-linking agent in this work. Cellulose acetate (CA) as an additive with plenty of polar groups was introduced by a simple solution blending to improve their electrochemical performance. The enhanced ion-dipole interaction of the polar groups with Li + ions in the composite polymer electrolytes was studied, which affected the carbonyl and ether vibrational mode and weakened the symmetric vibration band of ion pairs. The exothermic peak of solvents decomposition that related to lithium salts shifted to a low temperature. After the introduction of CA additive, PEGDA/CA GPE exhibited excellent electrochemical performance, including a high ionic conductivity up to 8.81 × 10 −3  S cm −1 at 30 °C, a high lithium ion transference number of 0.79 and an electrochemical window of 4.56 V. The electrode-electrolyte interface contact was improved due to the presence of CA with solvated viscosity. This study provides a new direction for the application of PEGDA and inspires that close attention should be paid to the interaction of Li + ions with different polar groups for novel polymer electrolytes designing. Graphical abstract: Image 1 Highlights: PEGDA is used as a matrix instead of a cross-linking agent in polymer electrolytes. The performance of PEGDA GPE is improved by the introduction of CA. Enhanced ion-dipole interaction contributes to improve ionic conductivity. The viscosity of solvated CA is beneficial for electrode-electrolyte contact.